Antioxidant activity of gamma irradiated Lactarius deliciosus L. from Northeast Portugal - Fernandes, Ângela (2012)
A diet rich in natural antioxidant compounds has been linked to a reduced risk of developing chronic oxidative stress-related diseases, including cancer and cardiovascular and neurodegenerative diseases. In addition to their highly appreciated nutitional value, mushrooms could be an interesting source of antioxidant compounds [1]. Nevertheless, their short shelf-life might be a limitation to the distribution and marketing of fresh mushrooms. Gamma irradiation could be an alternative to ensure the quality and extend mushrooms shelf-life, that has been used in several food products (Directive 1999/2/EC). Herein, the effects of gamma irradiation (0.5 and 1 kGy performed in a 60Co experimental equipment) and storage time (0, 4 and 8 days at 4 ºC) in antioxidant potential of the wild edible mushroom Lactarius deliciousus L. collected in Trás-os-Montes, Northeast Portugal, were evaluated for the first time. The antioxidant properties were evaluated through scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, reducing power (RP), inhibition of lipid peroxidation using thiobarbituric acid reactive substances (TBARS) and β-carotene-linoleate model systems. Data obtained show influence of storage time and irradiation dose over antioxidant activity. Some effects were clearly observed, such as the case of the highest antioxidant potential observed in irradiated samples (with both doses) when compared to non-irradiated ones (control) at 0 days. Therefore, the application of gamma irradiation seemed to be advantageous for the assayed antioxidant methods, but further studied are necessary to understand the mentioned effects.